Ответы и объяснения

Лучший Ответ!
2014-01-23T10:21:26+04:00
(6х+1)²+2(х-1)(х²+х+1)-2(х+1)³=26(6х+1)(6х+1)+(2х-2)(х²+х+1)-2((х+1)(х+1)(х+1))=26
36х²+6х+6х+1+2х³+2х²+2х-2х²-2х-2((х²+х+х+1)(х+1)=26
36х
²+12х-1+2х³-2(х³+х²+х²+х²+х²+х²+х²+1)=26
36х²+12х-1+2х³-2х³-2х²-2х²-2х²-2х²-2х²-2х²-2=26
12х-3+24х²=26
12х+24х²=26+3
12х+24х²=29
12х=29                            или                          24х²=29
х=29:12                           или                          х²=29:24
х=2 5/12                          или                          х²=1 5/24
                                                                           
ответ х= 2 5/12 или х²=1 5/24